Performance Of Reinforced Concrete Beam With Embedded Galvanized Steel As Lightning Down Conductor Cable - Rahim, Mustaqqim Abdul (2019)
Due to current problem with existing lightning protection systems such corrosion and stolen cable, a new system that can be installed within concrete structures has been introduced by the International of Electrotechnical Commission (IEC). However, detailed installation guidelines were not provided and previous study indicated that improper installation techniques and unsuitable materials embedded inside the concrete structure could cause physical damage to the concrete. Therefore, a newly proposed arrangement of galvanized steel cable was studied in this research. The impact of lightning simulation towards the concrete beams was determined. Concrete beams of 200 x 300 x 1200 mm sizes were used and several tests were conducted in order to investigate the performance of concrete beams. It was found that; very minimum temperature increases inside the concrete beams that were charged with high electric current. From the frequency test, reduction of natural frequency before and after the lightning simulation can be assume as negligible.